2019
DOI: 10.3390/d12010001
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth and Insecticide Residues of Honey Bees in Tropical Agricultural Landscapes

Abstract: Global decline of pollinators, especially bees, has been documented in many countries. Several causes such as land-use change and agricultural intensification are reported to be the main drivers of the decline. The objective of this study was to investigate the effect of land use on honey bee and stingless bee populations. Research was conducted in Bogor and Malang to compare between two different geographical areas. Managed bees such as honey bees (Apis cerana and A. mellifera) and stingless bees (Tetragonula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…This research was conducted to study the bee diversity that are being managed by beekeepers across Indonesia and to investigate the beekeepers' perspectives on the factors that affect bee populations and their products. Previous research found that the population of honey bees is affected by habitat types and that beekeepers prefer to put their hives isolated from agricultural areas [34]. There was indication of the population decline of A. cerana in East Java, although the result was not conclusive.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…This research was conducted to study the bee diversity that are being managed by beekeepers across Indonesia and to investigate the beekeepers' perspectives on the factors that affect bee populations and their products. Previous research found that the population of honey bees is affected by habitat types and that beekeepers prefer to put their hives isolated from agricultural areas [34]. There was indication of the population decline of A. cerana in East Java, although the result was not conclusive.…”
Section: Introductionmentioning
confidence: 80%
“…The threat from insecticides such as neonicotinoid has been reported to increase the mortality in honey bees by impairing their homing ability [15]. Previous studies in Europe also detected residue pesticide in honey bees products in countries such as in Spain [35], Germany [36], Greece [37], and France [38], while in Indonesia, traces of residues were detected, albeit at very low concentrations [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [13] identified positive habitat effects while studying the impact of land use patterns, agricultural intensification and insecticides residues on honey bees (Apis cerana and A. mellifera) and stingless bees (Tetragonula laeviceps) in Indonesia (Bogor and Malang regions). They discovered certain habitat types alleviate bee stress and promote colony growth and queen reproductive output, especially forests with abundant sources of honeydew.…”
mentioning
confidence: 99%